Contraceptive Use Among Women Of Reproductive Age And The Number Of Ideal Children In West Java - Ade Saputra Nasution; Resty Jayanti; Andreanda Nasution; Darojad Nurjoni Agung Nugroho; Heru Heru; Evalina Franciska Hutasoit (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: The use of contraceptives for couples of childbearing ages is influential on the birth. More children born means the more spending to support the children, and eventually impacting the health of the children. The perspective on the ideal number of children for parents is influenced by demographic, social and economic conditions. This study examines the extent of the relationship between demographic conditions, contraceptive use, and access to family planning services to the ideal number of children among couples of childbearing age in West Java Province. Methods: This type of research is analysis of an existing dataset. This study uses the 2017 IDHS data and the sample population is women of reproductive age 15-49 years who are registered in the IDHS in West Java Province. Data processing were conducted on August-November 2020 using chi square data analysis. Results: The results showed that there was a relationship between the use of contraceptives and the ideal number of children (p-value 0,032). On the other hand, other demographic and social economic variable of the couples of childbearing ages: education (p-value 0,076), knowledge of contraceptive (p-value 0,737), wealth (p-value 0,489) and health information (p-value 0,413) shows no relationship with the ideal number of children. Conclusion: Among demographic and social economic variable of the couples of childbearing ages, only contraceptive use shows a relationships with ideal number of children. In order to reduce fertility rates, more campaign regarding family planning especially for couples of childbearing ages, religious leaders, the customs and the community leaders are needed.